Secagem convectiva e secagem micro-ondas-vácuo de yacon osmoticamente pré-tratado - Lopes, Francemir José (2016)
The present work aimed to study the convective drying and microwave-vacuum of yacon preceded by pulsed vacuum osmotic dehydration. The first article presents the results of the convective drying of yacon, while the second article presents results of microwave-vacuum drying.The influence of the type of drying and use of osmotic dehydration process the fructanretention, shrinkage, color, rehydration capacity, diffusivity and drying time. Were analyzed The pulsed vacuum osmotic dehydration (PVOD) was performed with sorbitol solution, 38 °Brix, 35 °C and 681 mmHg vacuum pulse in the first 10 minutes of dehydration. In the convective drying,the temperatures were 40; 50; 60 and 70°C and constant air velocity 0.5 ms-1.The drying time wasreducedwithincrement temperature and the use of PVOD.The consideration of shrinkage resulted in a better fitness of the drying kinetics. The PVOD was effective to reduce drying time and shrinkage, but results in a browned sample with lower retention of fructooligosaccharides(FOS). Experiments in microwave-vacuum are based on experimental design with three 3k power density levels (PD) (3.6, 6.3 and 9.8 Wg-1), and three vacuum pressure (VP) (0, 300 and 600 mmHg). The results showed that increasing microwave power density resulted in lower and process times were decrease with the use of PVOD. Moreover, power density showed a positive influence in retention of FOS and shrinkage. The vacuum pressure was also significant effect for retention of FOS in pretreated samples and helped drying. The sugar presence in PVOD seems to browning of yacon. Power density of 9.8 Wg-1 and vacuum pressure of 600 mmHg osmotically dehydrated samples stood out in the microwave vacuum drying of yacon, resulting in superior product compared to convective drying.